A Membranome-Centered Approach Defines Novel Biomarkers for Cellular Subtypes in the Intervertebral Disc. (April 2020) - van den Akker, Guus G. H.; Eijssen, Lars M. T.; Richardson, Stephen M.; Rhijn, Lodewijk W. van; Hoyland, Judith A.; Welting, Tim J. M.; Voncken, Jan Willem
Objective: Lack of specific marker-sets prohibits definition and functional distinction of cellular subtypes in the intervertebral disc (IVD), such as those from the annulus fibrosus (AF) and the nucleus pulposus (NP). Design: We recently generated immortalized cell lines from human NP and AF tissues; these comprise a set of functionally distinct clonal subtypes. Whole transcriptome analyses were performed of 12 phenotypically distinct clonal cell lines (4× NP-Responder, 4× NP-nonResponder, 2× AF-Sheet forming, and 2× AF-nonSheet forming). Data sets were filtered for membrane-associated marker genes and compared to literature. Results: Comparison of our immortal cell lines to published primary NP, AF, and articular chondrocytes (AC) transcriptome datasets revealed preservation of AF and NP phenotypes. NP-specific membrane-associated genes were defined by comparison to AF cells in both the primary dataset (46 genes) and immortal cell-lines (161 genes). Definition of AF-specific membrane-associated genes yielded 125 primary AF cell and 92 immortal cell-line markers. Overlap between primary and immortal NP cells yielded high-confidence NP-specific marker genes for NP-R ( CLDN11, TMEFF2, CA12, ANXA2, CD44 ) and NP-nR (EFNA1, NETO2, SLC2A1). Overlap between AF and immortal AF subtypes yielded specific markers for AF-S ( COLEC12, LPAR1 ) and AF-nS ( CHIC1 ). Conclusions: The current study provides a reference platform for preclinical evaluation of novel membrane-associated cell type–specific markers in the IVD. Future research will focus on their biological relevance for IVD function in development, homeostasis, and degenerate conditions.